1997
DOI: 10.1088/0953-8984/9/45/008
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and electronic properties of a tight-binding lattice-gas model

Abstract: Thermodynamic and electronic properties are obtained for a lattice-gas model fluid with self-consistent, partial, occupation of its sites; the self consistency consists in obtaining ionic configurations from grand-canonical Monte Carlo simulations based on fits to the exact, electronic, tight-binding energies of isothermal ensembles of those same ionic configurations. The energy of an ion is found to be a concave-up function of its local coordination. Liquid-vapor coexistence densities and the electrical condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The weak dependence of T c * on ␣*, for the TB-HS model, reflects the saturation of the electronic energy with increasing average number of neighbors which was already discussed in our previous lattice-gas model. 4 Further, the saturation of the electronic energy with the number of neighbors is also reflected in the value of the critical density, which in a mean-field pair-interaction model would depend only on the HS contribution. In the TB-HS model, the electronic free energy per ion has a large curvature at intermediate values of the density, associated with the saturation effect; these densities are about three times smaller for ␣*ϭ2.0 than for ␣*ϭ3.89.…”
Section: A Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak dependence of T c * on ␣*, for the TB-HS model, reflects the saturation of the electronic energy with increasing average number of neighbors which was already discussed in our previous lattice-gas model. 4 Further, the saturation of the electronic energy with the number of neighbors is also reflected in the value of the critical density, which in a mean-field pair-interaction model would depend only on the HS contribution. In the TB-HS model, the electronic free energy per ion has a large curvature at intermediate values of the density, associated with the saturation effect; these densities are about three times smaller for ␣*ϭ2.0 than for ␣*ϭ3.89.…”
Section: A Phase Diagramsmentioning
confidence: 99%
“…We began with a oneelectron treatment. 4 Then, the effects of a Hubbard interaction among electrons was considered. 5 That work was recently reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Among the approximations in this theory, the importance of improving the mean-field approximation for atomic arrangements has been pointed out by Reinald-Falagán et al [11,12]. They concluded that it is important to treat the local atomic configuration beyond the mean-field approximation self-consistently with the electronic energy to reproduce the asymmetric feature of the LV coexistence curve.…”
Section: Discussionmentioning
confidence: 99%
“…the curve describing the boundary of the coexisting liquid and vapour phases on the volume versus temperature plane, is strongly asymmetric and the law of the rectilinear diameter breaks down over a large temperature range for fluid alkalis such as Rb and Cs. Among recent theoretical research in relation to the above experimental results, the work most relevant to the present paper is that by Reinaldo-Falagán et al [11,12]. In the earlier paper [11], using a model which is the single-particle version of the latticegas Hubbard model presented above, and a self-consistent method for determining the ionic configurations and the electronic energies, they obtained results for the thermodynamic and electronic properties of expanded alkali fluids which agree qualitatively with the experimental results.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation